Religion and technology in the 21st century : faith in the e-world - George, Susan, 1967- (Hershey, PA : Information Science Pub., 2006)
'This book examines the unique synergy between religion and technology, and explores the many ways that technology is shaping religious expression, as well as ways that religion is coming to influence technology'--Provided by publisher.
Keywords: Computers -- Religious aspects -- Christianity; Internet -- Religious aspects -- Christianity; Computers -- Religious aspects; Internet -- Religious aspects